Scanning laser Doppler vibrometry of the cranium when stimulated by a B71 bone transducer. (15th December 2018) - McLeod, R.W.J; Roberts, W.H.; Perry, I.A.; Richardson, B.E.; Culling, J.F.
Abstract: Scanning laser Doppler vibrometry (LDV) has been used extensively to investigate the movement of the middle and inner ear, but has never been used to measure vibrations from a bone transducer travelling over the skin, subcutaneous tissue and cranium in a live subject. Using three scanning laser Doppler vibrometers we measured the displacement of the cranium in 3D in a live subject when stimulated by a B71 bone transducer placed 55 mm posterior to the external auditory canal. Four pure tones (250 Hz, 500 Hz, 1000 Hz, 2000 Hz) were presented separately via the bone transducer. The displacement of the scalp was imaged in four different areas (Ipsilateral to the bone transducer in the temporoparietal region, contralateral temporoparietal region, occipital region and vertex) and linked to the phase of stimulation. Measured scalp motion was consistent with expected displacement of the underlying cranium. Rigid-body motion was the dominant mode of vibration at 250 Hz. At 1000 Hz a mass-spring effect was seen. At 500 Hz there was a transition frequency between vibration as a rigid-body and as a mass-spring. Higher frequencies (2000 Hz) showed that wave transmission was the primary vibrational mode of sound transmission over the cranium. These results broadly support previous research studies but open up potential areas of interest in the investigation of differing skull resonance frequencies.